FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI PELAKU UMKM TERHADAP LAPORAN KEUANGAN - Anni Safitri; Ade Shofa Novrina; Siska Dewi (Politeknik Negeri Semarang, 2022)
The purpose of this study was to analyze the effect of business duration, business scale, business turnover, and utilization of accounting information on financial statements. The sample used in this study was 100 respondents of UMKM actors in Pekalongan Regency who were taken using the simple random sampling method. This research approach uses a quantitative approach with descriptive analysis with data collection techniques in the form of questionnaire questions. The data used in this study are primary data and secondary data. Primary data is in the form of answers from respondents by means of questionnaires, while secondary data is obtained from information on UMKM data in Pekalongan Regency. Analysis of the data used is multiple linear regression analysis. The results of this study indicate that the length of business, business scale, and utilization of accounting information have a significant effect on financial statements. Meanwhile, business turnover has no significant effect on the financial statements.